Identity, profiles and pseudonyms in the digital environment - Mourby, M; Mackey, E (Amsterdam University Press, 2024)
The boundaries of personal data are determined by the concept of ‘identity’. Personal data, as defined under the GDPR, is information relating to an identified or identifiable natural person. In this chapter, we argue that the informational ‘identity’ of an identified/identifiable person is characterised by the potential for privacy impact. Our informational identity is, in essence, the sum of all the information which can impact our rights. We use profiles and pseudonyms as an illustration of this definition. Profiles permit scrutiny of an individual – and thus ‘identify’ them through the intrinsic privacy impact of this evaluation. Pseudonyms alone do not allow individuals to be evaluated, which is why they are not, in and of themselves, personal data.